2015
DOI: 10.3117/plantroot.9.70
|View full text |Cite
|
Sign up to set email alerts
|

Catechin production in roots of <i>Thujopsis dolabrata</i> var. <i>hondai</i> in soils on Mt. Hayachine with high Ni concentrations

Abstract: Mt. Hayachine in Iwate prefecture is characterized by serpentine site, which is known to have high concentrations of Ni. In general, few plants that can tolerate high concentrations of Ni can grow in serpentine soil. Thujopsis dolabrata var. hondai occurs naturally on Mt. Hayachine. In this study, we hypothesized that T. dolabrata var. hondai shows Ni tolerance due to detoxification by phenolics. We collected T. dolabrata var. hondai seedlings and root-zone soil from the Kadoma National Forest on Mt. Hayachine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…hondai is naturally distributed in serpentine soils with high Ni content. Okimura et al (2015) showed that catechin production in the roots of T. dolabrata var. hondai, which exists naturally in serpentine soil with high Ni concentration, increased in high Ni concentration soil as compared to those in other soil conditions, suggesting that the roots of T. dolabrata var.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…hondai is naturally distributed in serpentine soils with high Ni content. Okimura et al (2015) showed that catechin production in the roots of T. dolabrata var. hondai, which exists naturally in serpentine soil with high Ni concentration, increased in high Ni concentration soil as compared to those in other soil conditions, suggesting that the roots of T. dolabrata var.…”
mentioning
confidence: 99%
“…At any scale of study, we-root researchers-are interested in root traits, which contribute to plant functions, although studies at different scales may have different objectives depending on their focus, such as survival, growth, reproduction or harvest of individual plants, production, decomposition, soil formation, and retarding or driving succession through material cycling of ecosystems. This special issue contains four studies on roots of trees in Japan, on different themes and scales: the mechanisms of stress tolerance to excessive heavy metal soil (Okimura et al 2015), anatomical and morphological differentiation within a root system (Tawa and Takeda 2015), root biomass distribution patterns under competition (Hishi et al 2015), and response of tree organs to long-term N saturation (Nagakura et al 2015).…”
mentioning
confidence: 99%